(untitled) (Journal of Philosophy Culture and Political Science, 2018)
Kazakhstan in order do ender the top 50 most developed countries has to relook social-political development and economic growth, moral values in a new and different way. In this respect philosopical signitacance of M.Kh.Dulati’s creative work as a great philosopher, famous historian, versatil personality is not to be underappreciated. The article analyzes the significance in the history of the Kazakh national philosophy of the famous work «Tarikhi Rashidi», authored by M.Kh.Dulati, the outstanding personality of Turkish literature. The article discusses the philosophical ideas and scientific calculations M.H.Dulati, which are reflected not only in the era of globalization has become more complicated in the upbringing of the younger generation, who also provide the opportunity for in-depth study of the independent spirit of the people, his life, his social and spiritual portrait. In addition, the detailed analysis of the scientific views of a prominent thinker as the founder of the history of philosophy that influenced the development of modern Kazakh philosophy.